Vulnerabilities Rethinking Medicine Rights and Humanities in Post-pandemic - Achella, Stefania; Marazia, Chantal (Cham : Springer International Publishing : Imprint: Springer, 2023)
Drawing from a wide array of disciplinary perspectives and geographical contexts, this volume offers new insights for critically engaging with the problem of vulnerability. The essays here contained take the move from the COVID-19 pandemic, in order to explore the inherent vulnerability of individuals, but also of social, economic and political systems, and probe the descriptive and prescriptive import of the concept. Each chapter provides a self-contained perspective on vulnerability, as well as a specific methodological framework for questioning its meaning. Taken together, the chapters combine into a multi-disciplinary toolkit for approaching the various forms and structures of vulnerability, with a special attention to the intersectional factors shaping the individual experience of it: from gender to age, from disability to mental illness, from hospitalisation to incarceration. The book explores the theoretical richness and complexity of the concept and proposes new analytical approaches to it, before illustrating its multifariousness through empirically grounded case studies. The closing section engages with "the future of vulnerability", as a hermeneutic, epistemological, and critical-normative perspective to be deployed beyond the domain of global crises and emergencies. The volume is primarily intended as a reference for scholars in the human, social and health sciences. The accessible structure and plain language of the chapters make it also a valuable didactic resource for graduate courses in philosophy, the social sciences and public health.
Part I: What is Vulnerability -- 1.Vulnerability is said in many ways -- 2. Ethics in Scenes of Disaster -- 3. Humanity of the Human and the Politics of Vulnerability -- 4. Vulnerability and the End of the World -- 5. A Biosocial Perspective on (COVID-19) Pandemic Outbreaks: Interfaces of Biology and Social Determinants -- Part II: Who is Vulnerable? -- 6. Vulnerability and Gender fter COVID-19 -- 7. Phenomenology of Vulnerability: a Person-centred Approach -- 8. (In-) Visibility of Children and their Psychosocial Vulnerability - the Narrowed Discourse on Children in the First Year of the Pandemic in Germany -- 9. Social Inequality in Child Health and Development - Before and after the COVID-19 Pandemic -- 10. The (Crip) Art of Reworking Vulnerability - and Perhaps, to Find a Way Out of It -- 11. "Total Institutions" as Litmus Test of Civilisation -- Part III. The future of Vulnerability -- 12. Vulnerable to Ourselves, or the Radicalized Disenchantment of Being -- 13. Pandemic Necropolitics: Vulnerability, Resilience, and the Crisis of Marginalization in the Liberal Democratic State -- 14. Vulnerability as a New Perspective on Ethical Challenges in Healthcare -- 15. Vulnerability, Interest Convergence, and the COVID-19 Pandemic: Lessons from the Future.
Keywords: Bioethics; Medical policy; Ethics; Quality of life; Medical Ethics; Science -- Philosophy; Bioethics; Health Policy; Moral Philosophy and Applied Ethics; Quality of Life Research; Medical Ethics; Philosophy of Science